2012
DOI: 10.1210/en.2011-1909
|View full text |Cite
|
Sign up to set email alerts
|

Role of Fibroblast Growth Factor 21 (FGF21) in Undernutrition-Related Attenuation of Growth in Mice

Abstract: Reduced caloric intake in mammals causes reduced skeletal growth and GH insensitivity. However, the underlying molecular mechanisms are not fully elucidated. The aim of this study was to determine whether the increased activity of fibroblast growth factor 21 (FGF21) during chronic undernutrition in mice causes GH insensitivity and growth failure. After 4 wk of food restriction, fgf21 knockout (KO) mice exhibited greater body and tibial growth than their wild-type (WT) littermates. Daily injections of recombina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
67
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(78 citation statements)
references
References 18 publications
8
67
3
Order By: Relevance
“…Transgenic mice overexpressing FGF21 exhibit shorter body length and tibiae when compared with wild-type mice (6). We have previously demonstrated that FGF21 expression is increased in the liver and in the growth plate of food-restricted wild-type mice (17). In food-restricted Fgf21 knock-out mice, the attenuated reduction of tibial growth and tibial growth plate thickness (compared with food-restricted wild-type mice) indicates that the increased expression of systemic FGF21 in food-restricted wild-type mice is causally related to the suppressed growth plate chondrogenesis and, in turn, suppressed longitudinal bone growth.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Transgenic mice overexpressing FGF21 exhibit shorter body length and tibiae when compared with wild-type mice (6). We have previously demonstrated that FGF21 expression is increased in the liver and in the growth plate of food-restricted wild-type mice (17). In food-restricted Fgf21 knock-out mice, the attenuated reduction of tibial growth and tibial growth plate thickness (compared with food-restricted wild-type mice) indicates that the increased expression of systemic FGF21 in food-restricted wild-type mice is causally related to the suppressed growth plate chondrogenesis and, in turn, suppressed longitudinal bone growth.…”
Section: Discussionmentioning
confidence: 96%
“…In a previous study we demonstrated that mice undergoing 4 weeks of food restriction exhibited increased expression of Fgf21 (both in the liver and in the growth plate), growth hormone (GH) 3 insensitivity, and a concomitant reduction of their body linear growth and growth plate chondrogenesis (17). Interest-ingly, food-restricted Fgf21 knock-out mice experienced an attenuated reduction of their linear growth, tibial growth, and tibial growth plate thickness when compared with food-restricted wild-type mice.…”
mentioning
confidence: 99%
“…The effect appears to be mediated in part by FGF21-dependent inhibition of growth hormone (GH) signaling in the liver, resulting in reduced hepatic IGF1 secretion (49)(50)(51). A separate study indicates that FGF21 contributes to the attenuation of growth during undernutrition (52). Our results support and extend these data and demonstrate that FGF21 plays an essential role in linking dietary protein intake to body growth and composition.…”
Section: Discussionsupporting
confidence: 70%
“…Transgenic (Tg) mice overexpressing FGF21 are markedly smaller than wild-type mice and have a corresponding decrease in circulating IGF-1 concentrations despite having elevated growth hormone (GH) levels (Inagaki et al, 2008). Conversely, FGF21-knockout mice grow more than wild-type mice under conditions of nutrient deprivation (Kubicky et al, 2012). In liver, FGF21 inhibits the GH signaling pathway by blocking JAK2-mediated phosphorylation and nuclear translocation of the transcription factor, STAT5.…”
Section: Introductionmentioning
confidence: 99%